Coffee Cup - Gardella, Lorrie Greenhouse (Social Work in 42 Objects (and More), 2017)
Can the story of social work be told through Objects? Might a collection of objects be more illuminating than a formal text book or a dry definition? In this engaging, photographic book, Mark Doel curates a collection of 127 objects contributed by people from around the globe to evoke a sense of social work - past, present and future. Written as a Guide to an Exhibition of Social Work, this is the ideal book to introduce social work to newcomers, and to entertain those with long experience of the profession. The objects are presented by a diverse group of people with different perspectives on social work, but with a common imagination.–From publisher.
Keywords: Political Science / Public Policy / Social Services & Welfare; Social Science / Social Work; dept.swk

Organizational practice with LGBT people - Colon, E. (Social Work Practice with Lesbian, Gay, Bisexual, and Transgender People, 2017)
Journal Abbreviation: Soc. Work Pract. with Lesbian, Gay, Bisexual, and Transgender People
Keywords: dept.swk

Waiting for shelter: Perspectives on a homeless shelter's procedures - Brown, Molly; Mihelicova, Martina; Lyons, Jennifer; DeFonzo, Jennifer; Torello, Samantha; Carrion, Andres; Ponce, Allison N. (Journal of Community Psychology, 2017)
Research on homeless shelter implementation is limited. Some shelters have lengthy waitlists, which raises important questions about implications of waitlists for individuals with immediate shelter needs. This study used qualitative methods to understand the experiences of shelter seekers who were on a shelter waitlist (N = 59), including individuals who entered the shelter from the waitlist, and those removed from the shelter waitlist for procedural reasons. The average waitlist time was nearly 3 weeks, and 22.0% stayed at least one night on the street or another public place while on the waitlist. Responses to open-ended questions regarding barriers and effectiveness of the shelter referral procedures revealed 4 themes: procedural challenges, procedural benefits, benefits of the temporary stay, and communication challenges. Further research is needed to inform shelter implementation on a larger scale in accordance with current community-wide efforts to coordinate shelter services.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-373-730-428-961 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; female; human; major clinical study; male; night; patient referral; qualitative analysis

Development of the citizens measure into a tool to guide clinical practice and its utility for case managers - Bellamy, Chyrell; Kriegel, Liat; Barrenger, Stacey L.; Klimczak, Michele; Rakfeldt, Jaak; Benson, Victoria; Baker, Michaella; Benedict, Patricia; Williamson, Bridgett; MacIntyre, Gillian (American Journal of Psychiatric Rehabilitation, 2017)
A measure of citizenship was developed and validated by Rowe and colleagues (O’Connell, Clayton, & Rowe, 2017). The items clustered around the 5 Rs of citizenship as defined by Rowe et al.: relationships, rights, resources, roles, and rights, and a sense of belonging. Although a measure has its utility in clinical settings, to address time constraints and other administrative burdens expressed by providers in their day-to-day practice, a citizens tool was developed as a practical way that providers can enhance dialogue between providers and clients on citizenship for clients served in mental health and criminal justice reentry settings. This article describes the development of the tool, testing of the tool’s utility with case managers, and implications for practice. © 2017 Taylor & Francis.
8 citations (Crossref) [2023-10-31] Citation Key Alias: pop00114 tex.type: [object Object]
Keywords: Article; adult; case management; case manager; citizenship; clinical practice; community inclusion; community integration; dept.swk; evidence based medicine; female; human; major clinical study; male; marginalized communities; mental capacity; mental disease; mental health service; poverty; practical clinical tools; priority journal; psychological well-being; self concept; social support; socioeconomics; translational research

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Hungry on the inside: Prison food as concrete and symbolic punishment in a women’s prison - Smoyer, Amy B; Lopes, Giza (Punishment & Society, 2017)
Women’s perceptions of the prison experience and the punishing dimensions of their confinement are under-examined. To expand knowledge in this area, Sexton’s theory of penal consciousness is used to analyze formerly incarcerated women’s narratives about prison food. This analysis builds understanding about the lived experience of incarceration by explicating one dimension of prisoners’ understandings and perceptions of punishment. Women’s narratives describe both concrete and symbolic punishments associated with food. Participants spoke about poorly designed, sloppy food systems that left them feeling uncared for, ignored, frustrated, and humiliated. Women articulate experiences of hunger that reflect both a deprivation of adequate food and a rationing of humane attentions. These punishing perceptions may inhibit the efforts of social service and health providers to engage incarcerated and formerly incarcerated women in care. In contrast, exceptional participant narratives about positive, non-punishing food experiences suggest that ameliorated food systems could improve the lived experience of incarceration and promote the engagement in services that is needed to improve the outcomes of incarcerated and formerly incarcerated women.
54 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000395402500006, lens.org/015-306-581-234-40X tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prison; punishment; women

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

A "Just Sense of Well-Being": Social Work's Unifying Purpose in Action. - Keenan, Elizabeth King; Limone, Christine; Sandoval, Silvia L (Social work, 2017)
For over a century the social work profession has had a dual purpose, to promote both human well-being and social justice, but we have not found research that explores how social workers understand and work toward both purposes across multiple practice roles and settings. Authors of this article conducted qualitative research to examine how 18 social workers in various roles and settings understand and implement both purposes in their practice. Instead of a dual purpose, participants described a unifying purpose: a "just sense of well-being" that transcends role and setting. Valuing the dignity and worth of all human beings frames and fuels their work toward a just sense of well-being through three interactive themes: challenging injustice on every level; constructing justice through relationship and resource organizing; and constructing justice through the creation of accepting environments where professionals, clients, and community members can reflect and question, and change mind-sets and actions. Participants provided an array of possibilities for action with clients, professionals, and public leaders within organizations and communities. The implication here is that social workers are charged to reinvigorate purpose and values back into practice with value-based assessment thinking that frames possibilities for action across methods and settings. Copyright © 2016 National Association of Social Workers.
5 citations (Crossref) [2023-10-31] Place: United States Keenan, Elizabeth King. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Limone, Christine. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Sandoval, Silvia L. School for Social Work, Smith College, Northampton, MA, USA.
Keywords: *Professional Role/px [Psychology]; *Social Justice/px [Psychology]; *Social Work/mt [Methods]; *Social Workers/px [Psychology]; Adult; Female; Humans; Male; Middle Aged; Professional Role; Qualitative Research; Social Justice; Social Work; Social Workers; Social justice; Social work practice; Values; Well-being; adult; dept.swk; dual purpose; female; human; human dignity; human experiment; leadership; male; middle aged; occupation; organization; procedures; professional standard; psychology; qualitative research; social justice; social work; social work practice; social worker; thinking; wellbeing

Responding to the oppression of addiction: Canadian social work perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2017)
Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; therapy; Social Work; Canada

Caring for the child welfare client: am I good enough? - Hoffler, Steven J (Smith College Studies in Social Work, 2017)
Given the demographics of youth served by the child welfare system, culturally responsive approaches are critical to effective social work practice and desperately needed. Like many adolescents who grow up in the child welfare system, Paul, a White adolescent male in foster care, was beset by a lack of adequate environmental resources and multiple stressors and had little hope or motivation to work on improving his situation. This article highlights the author's use of self as an African American male therapist who worked with Paul, using a Winnicottian and caring framework. Because child welfare workers are often overburdened by the demands of work, including large caseloads and clients with few to no resources, they find it difficult to consistently provide empathic and caring behaviors for their clients. The author highlights his therapeutic work and struggles with Paul and offers cultural insights and Winnicottian strategies when working with adolescents in the child welfare system who are ultimately in need of permanency and stability.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-860-273-285-190 tex.type: [object Object]
Keywords: Caring; Winnicott; child welfare; culture; dept.swk

Prison food in Denmark: Normal responsibility or ethnocentric imaginations? - Minke, Linda Kjær; Smoyer, Amy B. (Scandinavian penal history, culture and prison practice - Embraced by the welfare state?, 2017)
This book draws on historical and cross-disciplinary studies to critically examine penal practices in Scandinavia. The Nordic countries are often hailed by international observers as ‘model societies’, with egalitarian welfare policies, low rates of poverty, humane social policies and human rights...
Citation Key Alias: lens.org/077-884-123-268-809, minkePrisonFoodDenmark2017a
Keywords: dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-482-460-077-460 tex.type: [object Object]
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-695-656-280-425 tex.type: [object Object]
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Building a bicultural bridge - Rodriguez-Keyes, Elizabeth; Piepenbring, Julie (Smith College Studies in Social Work, 2017)
The balancing act of living between two cultures can have a significant impact on the development of adolescent Latinas living in the United States. Many adolescent Latinas, particularly second generation, live with two sets of cultural values that are often in conflict with one another. This case study illustrates the importance of understanding the impact of acculturation on the individual and the family. Issues of identity, biculturalism, and bilingualismspecifically the phenomenon of language switchingare dismantled in this case study to gain deeper insight into the unique experience that second-generation Latinas undergo when negotiating two cultural orientations. These findings are important to consider when working with the Latino population as they represent one of the largest immigrant groups and the most rapidly growing group in the United States.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-329-811-473-861 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Latinas; adolescent; biculturalism; bilingual psychotherapy; cultural identity; dept.swk; language switching